Pengaruh Kadar Protein Pakan yang Berbeda terhadap Pertumbuhan Ikan Tambakan (Helostoma temminckii) - Retno Cahya Mukti; Yulisman Yulisman; Mohamad Amin; Rahyu Permata Sari (Jurnal Sumberdaya Akuatik Indopasifik, 2023)
Kissing gourami culture has begun to be developed to reduce the dependence on natural catches. Many factors that are influence fish culture. One of those is the availability of sufficient quantity and quality feed. Protein is an important nutrient that supports fish growth and affects feed prices. The protein requirement for each fish needs to be known as a basis for formulating feed. This research aims to determine the optimum feed protein level for kissing gourami. This study used a completely randomized design with five treatments and three replications. The treatment given is different levels of feed protein, consisting of 25% (P0), 30% (P1), 35% (P2), 40% (P3), and 45% (P4). The result showed that feed protein level 35% (P2) gave the best result for kissing gourami which resulted a absolute weight growth of 0.45 g, absolute length growth of 0.24 cm, protein efficiency ratio of 0.49, and feed efficiency of 17.11%.